MAINSTREAMING OF CHILDREN WITH LEARNING DIFFICULTIES: A STUDY OF SCHOOLS OF KOLKATA, INDIA - Arundhati Sarkar; Elizabeth Dey, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Any mainstream school’s trajectory of ‘Inclusive Education’ is dependent on the key factors playing out their roles for the actualisation of the proposed concept. The concept of ‘Inclusive Education’ envisions an environment where key factors: educators, administrators, and educational policies cater to diverse learners in an all-inclusive learning environment. ‘Mainstreaming’ of Children with Learning Difficulties (LD) in a system of ‘Inclusive Education’(IE) enhance the quality of learning of students with Learning Difficulties as well as those without. In this context, the paper examines classroom teachers’ attitude regarding ‘Inclusive Education’ in selected mainstream schools of Kolkata, West Bengal, India. A study was conducted with the help of a questionnaire schedule administered on 100 teachers. Responses to crucial questions were statistically computed by Chi-Square Test, interpreted and analysed. Of the two hypotheses drawn for study, the first states that mainstream school teachers ‘attitude towards Children with LD will be positive. The second hypothesis states that teachers will show a positive attitude toward providing additional guidance to children with LD in mainstream classrooms. The majority of responses supported the first hypothesis but rejected the second. Interviews of the respondents were recorded for a qualitative analysis, as well. Emerging traits from quantitative and qualitative analyses are discussed in the manuscript. This study may have implications for an expansive and in-depth research into the apprehensions of teachers of Secondary schools and lacunae in the education system to make ‘Inclusive Education’s success.